2019
DOI: 10.17696/2318-3691.26.1.2019.1241
|View full text |Cite
|
Sign up to set email alerts
|

Adesão e rejeição à consulta puerperal por mulheres de uma unidade básica de saúde da família

Abstract: Introdução: A primeira consulta puerperal deve ser realizada de sete a dez dias após o parto para uma completa avaliação da mãe e do recém-nascido, indicando precocemente alterações inesperadas, prevenindo agravos e controlando as taxas de morbimortalidade da criança e da mulher. Contudo, apesar de prioridade no âmbito de saúde pública, o retorno da mulher e a primeira ida do filho às consultas pósparto ainda são reduzidas. Objetivo: Identificar a motivação da adesão e rejeição da primeira consulta puerperal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 7 publications
(10 reference statements)
2
9
1
5
Order By: Relevance
“…11 There was predominance of puerperal women who did not have their own income for performing unpaid domestic activities or being students (52.6%). These results are in accordance with data found in the literature, which showed that 49.4 to 77.7% 12,14,19,21 of the puerperal women devoted their time to household activities and did not have their own income. Low income was associated with non-adherence to postpartum consultations in the southern region of Brazil 11 ; however, there was no association between income/occupation and adherence to the puerperal consultation in the study sample.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…11 There was predominance of puerperal women who did not have their own income for performing unpaid domestic activities or being students (52.6%). These results are in accordance with data found in the literature, which showed that 49.4 to 77.7% 12,14,19,21 of the puerperal women devoted their time to household activities and did not have their own income. Low income was associated with non-adherence to postpartum consultations in the southern region of Brazil 11 ; however, there was no association between income/occupation and adherence to the puerperal consultation in the study sample.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed a low rate of adherence to the puerperal consultation (34.7%), when compared to rates found in studies carried out in Mato Grosso do Sul (43.1%), 12 in the municipality of Botucatu, where the adhesion rate was 46.9% in the BHUs and 69.7% in the FHS 25 , in the state of Paraná (51,1%) 26 and in the southern region of Brazil (75.2%). 11 However, the index found is within the rate pointed out in a literature review study that found adherence rates ranging from 16.8 to 58%.…”
Section: Coefficientcontrasting
confidence: 73%
See 3 more Smart Citations